A9.02 Heat shock protein 90 plasma levels correlate with disease activity, skeletal muscle, lung and heart involvement in idiopathic inflammatory myopathies. (24th February 2016) - Storkanova, H; Krystufkova, O; Klein, M; Mann, H; Vernerova, L; Spiritovic, M; Zamecnik, J; Pavelka, K; Senolt, L; Vencovsky, J; Tomcik, M
Abstract : Background: Heat shock proteins (Hsps) are molecular chaperones playing a key role in muscle physiology, adaptation to exercise or stress, and in activation of inflammatory cells. Increased Hsp90 expression was demonstrated in regenerating and atrophic muscle fibres, and in inflammatory infiltrates. The aim of this study was to evaluate Hsp90 in the circulation of patients with idiopathic inflammatory myopathies (IIM) and characterise its potential association with IIM-related features. Methods: A total of 277 patients with IIM (198 females, 79 males; mean age 54.8; disease duration 4.1 years; dermatomyositis (DM, 104), polymyositis (PM, 104) cancer associated myositis (CAM, 42), necrotizing myopathy (IMNM, 27)) and 100 healthy individuals matched by age/sex were included. Plasma levels of Hsp90 were measured by ELISA (eBioscience, Vienna, Austria). Data are presented as median (IQR). Results: Extracellular Hsp90 was increased in IIM patients compared to healthy controls (20.2 (14.3–40.1) vs. 9.2 (7.2–12.6) ng/ml, p < 0.0001), and between individual subsets of IIM and healthy controls (PM: 19.4 (14.5–40.4), DM: 22.4 (14.3–43.5), CAM: 19.1 (12.3–29.8), IMNM: 19.6 (15.7–50.0) ng/ml, p < 0.0001 for all). Hsp90 levels in all patients positively correlated with levels of LD (r = 0.551, p < 0.0001), AST (r = 0.372, p < 0.0001), ALT (r = 0.158, p = 0.009). Increased Hsp90 was associated with decreased MMT8 values (r=-0.136, p = 0.029), in particular with proximal muscles. Hsp90 positively correlated with patient and doctor disease activity (r = 0.222, p = 0.0004; r = 0.217, p = 0.0005, respectively), pulmonary (r = 0.201, p = 0.001) and muscle disease activity (r = 0.146, p = 0.018), MITAX (r = 0.175, p = 0.005), MYOACT (r = 0.159, p = 0.012), and with MDI extent (r = 0.215, p = 0.003)/severity (r = 0.120, p = 0.041). Higher Hsp90 was found in patients with IIM-associated interstitial lung disease, cardiac involvement and dysphagia (25.4 vs. 18.9, p = 0.004; 27.5 vs. 19.3, p = 0.004; 25.0 vs. 18.2, p = 0.018, respectively). Increased Hsp90 was associated with higher prednisone equivalent dose (r = 0.180, p = 0.007) and treatment with DMARDs (22.0 vs. 18.9, p = 0.013). Conclusions: We demonstrate increased extracellular Hsp90 in IIM patients that is associated with damage and disease activity, with the involvement of proximal skeletal muscles, the heart and lungs. Hsp90 might become a useful biomarker of disease activity and muscle involvement in IIM. Acknowledgement: Supported by BT Cure and MHCR 023728.